Managing The Efficiency of Public Transport in The Silesian Voivodeship - Nicoletta BASKIEWICZ (Communications of International Proceedings, 2022)
The aim of the article is to analyze the effectiveness of the organization of modern public transport. This goal will be achieved through the analysis of available literature sources, including scientific publications and publications as well as websites dealing with this subject. Part of the empirical research concerns the organization of public transport in the Silesia Voivodship.   The basic research methods used in the creation of the article are: the method of analyzing the literature on the subject and the comparative method, allowing to summarize the views of many authors on the analyzed problem. For the purposes of the study, the method of analyzing documents and statistical data was also used, both methods allowed to present the functioning of public transport in the Silesia Voivodeship compared to other voivodeships, an additional research method allowing for a detailed diagnosis was the method of a diagnostic survey
Keywords: Collective Transport; Efficiency; Efficiency Management; Transport Efficiency